EXPLORING THE ROLE OF OXYTOCIN IN ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD): A LITERATURE REVIEW - Rahiq A. Alyahya, Mohamed O. Mohamed , Batool A. Alkhalifah , Sarah S. AlKhaldi , Amany M shehata, Sokara Ali, Mohamed R. Eletmany (Chelonian Research Foundation, 2024)
In addition to significant social difficulties, attention deficit hyperactivity disorder (ADHD) is a common mental illness characterized by impulsivity, hyperactivity, and inattention. Pharmacological interventions, the mainstay of traditional treatments, can have serious side effects and adverse consequences. Moreover, recent research has started to investigate another potential treatment for regulating ADHD. Oxytocin is known for its function in social cognition, behavior, emotional control, stress reduction, and social bonding. A few studies directly connected the oxytocin levels and OXTR gene variants with ADHD symptom control particularly in humans. This review summarizes current research and emphasizes the special potential of oxytocin as a target for ADHD treatment. By highlighting the need for more targeted research to confirm the benefits of oxytocin, new therapeutic avenues that may be less harmful than currently prescribed drugs become accessible.